The Effectiveness of a Group-Play–Based Program in Developing Linguistic Communication Skills among Children with Autism Spectrum Disorder (The International Journal of Educational Sciences and Arts, 2026)
The present study aimed to examine the effectiveness of a group-play–based program in developing linguistic communication skills among children with Autism Spectrum Disorder (ASD). The study was conducted on a sample of 32 children with ASD, aged between 4 and 6 years, with a mean age of 5.6 years and a standard deviation of 0.87. The participants were equally assigned to an experimental group and a control group. A quasi-experimental design was employed to implement the study procedures. The study instruments included the Linguistic Communication Scale (developed by the researcher) and the group-play–based program (designed by the researcher). The findings revealed the effectiveness of the program, as statistically significant differences were found between the pre-test and post-test mean ranks of the experimental group on the Linguistic Communication Scale in favor of the post-test. Furthermore, statistically significant differences were observed between the experimental and control groups on the post-test in favor of the experimental group. However, no statistically significant differences were found between the post-test and follow-up test scores of the experimental group. The study recommended the adoption of group play as an effective strategy to enhance linguistic communication skills among children with ASD.
Keywords: Group -Play; Based -Linguistic Communication Skills; Autism Spectrum Disorder